COVI-Prim Longitudinal Survey: Experiences of Primary Care Physicians During the Early Phase of the COVID-19 Pandemic - Schaffler-Schaden, Dagmar; Mergenthal, Karola; Avian, Alexander; Huter, Sebastian; Spary-Kainz, Ulrike; Bachler, Herbert; Flamm, Maria; Siebenhofer, Andrea (Frontiers in Medicine, 2022)
Background: General practitioners are the mainstay of primary care and play a critical role in pandemics. This international study aimed to explore changes in the workload, interactions with patients and colleagues, and self-confidence and concerns of general practitioners during the first wave of the COVID-19 pandemic. Methods: An online survey was conducted among general practitioners in Austria and Germany. Participants were asked to answer a basic questionnaire and participate in a subsequent longitudinal survey containing closed and open-ended items. All data were pseudonymized. Results: Overall, 723 general practitioners from Austria and Germany took part in the longitudinal survey over a period of 12 weeks (3rd April-2nd July 2020). The majority of GPs had less direct contact with patients at the beginning of the survey (96% vs. 49% at the end of the study period). The routine work of GPs such as screenings and treating chronic diseases was significantly reduced in the beginning when doctors were mainly concerned with pandemic-related issues and had to care for the patients of GP colleagues that were in quarantine. Over the survey period, GPs’ self-confidence increased and their concerns about income loss decreased. Conclusions: Following a difficult initial phase when protective equipment and information were lacking, physicians in primary care demonstrated that they can adapt quickly to new situations. Experience using telemedicine should help them face future challenges and may help prevent potential shortfalls in the performance of routine work and the provision of care for chronically ill patients.